2019
DOI: 10.1039/c9cc02291k
|View full text |Cite
|
Sign up to set email alerts
|

Efficient visible-light driven N2 fixation over two-dimensional Sb/TiO2 composites

Abstract: Photochemical ammonia production under ambient conditions remains a grand challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…By combining the above CB and VB data of MIS and MoS 2 with that of band gap data achieved from the Kubleka Munk Function, the respective VB and CB of MIS and MoS 2 are calculated to be 1.30 eV and −0.08 eV, respectively. Consequently, since all the potentials are measured under pH = 7 condition, hence the reduction potential values for water and nitrogen at pH = 7 (NHE) were estimated to be E H + / H 2 0 = −0.41 eV and E N 2 / NH 3 0 = −0.76 eV by the equation: E 0 (pH=0) – 0.0591pH …”
Section: Results and Discussionmentioning
confidence: 99%
“…By combining the above CB and VB data of MIS and MoS 2 with that of band gap data achieved from the Kubleka Munk Function, the respective VB and CB of MIS and MoS 2 are calculated to be 1.30 eV and −0.08 eV, respectively. Consequently, since all the potentials are measured under pH = 7 condition, hence the reduction potential values for water and nitrogen at pH = 7 (NHE) were estimated to be E H + / H 2 0 = −0.41 eV and E N 2 / NH 3 0 = −0.76 eV by the equation: E 0 (pH=0) – 0.0591pH …”
Section: Results and Discussionmentioning
confidence: 99%
“…OVs enriched Bi2MoO6 [164] and bimetallic layered-doublehydroxide (LDH) (ZnCr-LDH, ZnAl-LDH, and NiAl-LDH) nanosheets [165] were produced via an alkali etching approach. Alternatively, ultrasound irradiation was also shown to create defects mainly due to cavitation and induced ultrasonication chemistry [46,[166][167][168].…”
Section: Force-induced Strategiesmentioning
confidence: 99%
“…The broad bandgap and fast recombination of the photoexcited charge carriers of TiO 2 severely reduce its utilization of light 94 . Creating TiO 2 ‐based heterostructures are an effective method to solve these problems, because heterostructures can induce spatial separation of charge carriers and increase the absorption of light 95–97 . Obviously, TiO 2 ‐based type‐II (with a staggered gap) heterostructures are effective for boosting photocatalytic NRR activity because of its appropriate band structure for charge separation.…”
Section: Advances In the Design And Synthesis Of Tio2‐based Catalysts For Nrrmentioning
confidence: 99%
“…Zhao et al . have reported that 2D Sb/amorphous TiO 2 heterostructures are capable for efficient photocatalytic N 2 fixation with methanol as a hole scavenger 97 . The hybrid catalyst with an Sb‐to‐TiO2 weight ratio of 1: 0.5 affords the largest NH 3 yield rate of 20.8 μmol h −1 g −1 .…”
Section: Advances In the Design And Synthesis Of Tio2‐based Catalysts For Nrrmentioning
confidence: 99%